2014
DOI: 10.1371/journal.pone.0112128
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Interaction Mechanism with Liposomes of gH625-Peptide Functionalized Dendrimers

Abstract: We have demonstrated that amide-based dendrimers functionalized with the membrane-interacting peptide gH625 derived from the herpes simplex virus type 1 (HSV-1) envelope glycoprotein H enter cells mainly through a non-active translocation mechanism. Herein, we investigate the interaction between the peptide-functionalized dendrimer and liposomes composed of PC/Chol using fluorescence spectroscopy, isothermal titration calorimetry, and surface plasmon resonance to get insights into the mechanism of internalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 71 publications
1
24
0
Order By: Relevance
“…The gH625-dendrimer presents a high affinity for the membrane bilayer and deeply penetrates the bilayer where it does not form holes. 20 Our previous data support the hypothesis that the interaction with the bilayer can be splitted into a rst adsorption step that leads to an increased macromolecule concentration on the membrane and a second insertion step which involves the penetration into the lipid bilayer and likely a conformational change of the peptide bound to the dendrimer which assumes a helical conformation when in a membrane mimetic environment. Clearly, the mechanism of lipid association is key in the translocation process and thus in cellular uptake.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…The gH625-dendrimer presents a high affinity for the membrane bilayer and deeply penetrates the bilayer where it does not form holes. 20 Our previous data support the hypothesis that the interaction with the bilayer can be splitted into a rst adsorption step that leads to an increased macromolecule concentration on the membrane and a second insertion step which involves the penetration into the lipid bilayer and likely a conformational change of the peptide bound to the dendrimer which assumes a helical conformation when in a membrane mimetic environment. Clearly, the mechanism of lipid association is key in the translocation process and thus in cellular uptake.…”
Section: Introductionsupporting
confidence: 79%
“…Further structural characterization to conrm the functionalization were performed as previously reported. 20…”
Section: Peptide-dendrimer Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 This peptide has proved to exhibit exceptional vector properties 9 and has been shown to be essentially internalized by a nonendocytic pathway avoiding endosomal entrapment. 7,[12][13][14][15][16][17] In recent studies, it was also shown to be able to cross the blood-brain barrier in vitro and in vivo. 18 gH625 is, therefore, a very good delivery vector 9 and its coupling to NPs may be exploited to change their internalization mechanism and in case of MNPs, to avoid or reduce their toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main applications of fusion peptides of enveloped viruses is as inhibitors of viral penetration. Their ability to directly interact with the hydrophobic surfaces present on cell membranes and/or fusion proteins allows them to interfere with virus entry . The inhibition mechanism is still unclear but it is likely that inhibition of infectivity is correlated to inactive aggregates formed between the fusogenic stretches present in the viral protein and in the peptides.…”
Section: Applications Of Membranotropic Peptidesmentioning
confidence: 99%